Egg yolk colour and retinol concentration of eggs from laying hens fed diets containing carrot and beetroot meal - Zanelatto de Souza, Laura Aline; D'avila Lima, Heder Jose; Martins, Renata Aparecida [UNESP]; Almeida Assuncao, Andrey Savio de [UNESP]; Nunes Junior, Donaldo Antonio [UNESP]; Silva, Willian Ferreira; Silva, Felipe Gomes da (Czech Academy Agricultural Sciences, 2019)
Compounds such as pigments, antioxidants, and pro-vitamins A are found in carrots and beetroots and could increase the nutritional value of eggs when added to diets for laying hens. This research evaluated retinol concentrations and egg yolk colour with addition of freeze-dried carrot (Daucus carota L.) and beetroot (Beta vulgaris L.) meal in the diets of 240 Hisex Brown laying hens. The hens were distributed in a completely randomized design in five groups according to five experimental diets: (1) maize and soybean meal; (2) sorghum and soybean meal; (3) sorghum and soybean meal plus 0.8% of freeze-dried carrot meal; (4) sorghum and soybean meal plus 0.8% of freeze-dried beetroot meal; (5) sorghum and soybean meal plus 0.4% of freeze-dried carrot meal and 0.4% freeze-dried beetroot meal. The diet containing maize and soybean meal resulted in a more intense egg yolk colour and higher retinol levels in comparison to other diets (P < 0.05). However, carrot meal increased egg yolk colour and beetroot meal increased egg yolk retinol concentration in comparison to sorghum and soybean meal diets (P < 0.05). The inclusion of 0.8% of the carrot and beetroot meal in the diet is not enough to reach the intensity of yolk colour and yolk retinol concentration obtained through the diet containing maize, however, it increases retinol level and yolk colour in comparison to the diet containing sorghum without carrot and beetroot meal.
Keywords: additive; Beta vulgaris L.; Daucus carota L.; sorghum; photography